Secondary bone grafting of alveolar clefts: a review of outcome at two centres in Australia and the UK. Issue 5 (June 2017) - Kumar, R.; Heggie, A.; Shand, J.; Dominguez-Gonzalez, S.; Kilpatrick, N.; Shah, J.
Abstract: Secondary alveolar bone grafting is a key procedure in comprehensive cleft services, the main objective of which is to allow the canine to erupt through the bone. We have assessed the outcomes of the procedure at two units, one in Australia and one in the UK. Success was measured using standardised indexes for radiological assessment (Bergland and Kindelan) and clinically by noting eruption of canines through the grafted sites. The two-year review indicated that the two units had comparably high success rates. Canines erupted through cleft sites in 27/28 sites in patients in the UK, and 26/28 in patients in Australia, and the radiological success using the indexes was also high. These rates are in line with international benchmarks.